Transforming Local Food Security through the Adoption of Organic Farming - Inna Martha Rumainum; Ratna Ningsi; Nurlailah Nurlailah; Orgenes Wagarefe; Amin Mbusango; Yunita Palinggi; Veronica L. Tuhumena; Mathias M. Mobilala (Universitas Lambung Mangkurat, 2026)
Local farmers in Bintuni District do not yet understand cultivation techniques properly, resulting in low agricultural production. The purpose of this training was to provide an understanding of organic farming and improve the skills of farmers from the Meyah tribe in the Bintuni District, Teluk Bintuni Regency, in making organic fertilizers and organic pesticides. The training used discussion and practice methods. During the discussion session, the Unipa PkM team presented agricultural cultivation techniques, organic farming, and pest and disease control. Participants were very enthusiastic in listening to the material presented and provided a lot of feedback regarding obstacles encountered in the field. In the practical session, participants were given the opportunity to make organic pesticides from garlic and papaya leaves. In the final activity, participants made organic fertilizer from weeds, kitchen waste (vegetable scraps, etc.), and organic fertilizer from market waste. Both methods were very effective because they generated community enthusiasm, as can be seen from the responses given. Based on respondent data, there was an 85% increase in understanding of organic farming and cultivation techniques.